Transmission of Aggregatibacter actinomycetemcomitans between Brazilian women with severe chronic periodontitis and their children - Rêgo, Rodrigo Otávio Citó César; Spolidório, Denise Madalena Palomari [UNESP]; Salvador, Sérgio Luiz de Souza; Cirelli, Joni Augusto [UNESP] (My University, 2007)
This study evaluated the transmission of Aggregatibacter actinomycetemcomitans (Aa) in women with severe chronic periodontitis and their children. Thirty women (mean age = 36.1±6.0 years) who were mothers of at least one child aged 7 to 16 years were enrolled. In order to investigate mother-child transmission of Aa, the children were also evaluated when their mothers were colonized by the bacterium. Subgingival plaque samples of each woman were collected from 3 sites (mean probing depth of 7.3±1.2 mm and mean clinical attachment level of 7.9±1.5 mm) and pooled in reduced transport fluid (RTF). These samples were processed, inoculated onto TSBVagar selective medium and incubated at 37°C in microaerophilic atmosphere for 5 days. Aa was identified on the basis of colony morphology, Gram staining, catalase and oxidase reactions. Aa was found in 8 out of 30 women. Therefore, 8 children from these women (mean age= 12 ± 3.7 years) were evaluated, but Aa was found only in 2 of them. Aa strains of the two mother-child pairs were evaluated by arbitrarily-primed polymerase chain reaction (AP-PCR), although it was not found similarity between the amplitypes of each pair. No Aa transmission was found between Brazilian women with severe chronic periodontitis and their children.
Keywords: Aggregatibacter actinomycetemcomitans; Families; Microbiology; Periodontal diseases; Transmission; Actinobacillus actinomycetemcomitans; Actinobacillus infection; adolescent; adult; bacterial count; Brazil; child; chronic periodontitis; disease transmission; female; human; male; microbiology; tooth plaque; Actinobacillus Infections; Adolescent; Adult; Child; Chronic Periodontitis; Colony Count, Microbial; Dental Plaque; Female; Humans; Infectious Disease Transmission, Vertical; Male